Method for recycling iron phosphate from chemical nickel plating waste liquid
Through electrolytic pretreatment, Fenton oxidation and electrofenton oxidation steps, combined with the surface-modified coated nano zero-valent iron Fenton catalyst, the problems of low iron phosphate recovery and poor catalyst stability in electroless nickel plating waste liquid are solved. It realizes efficient recycling and high-purity iron phosphate production, suitable for industrial applications and meets environmental standards.
Patent Information
- Application Number
- CN202411481560.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the recovery rate of iron phosphate in electroless nickel plating waste liquid is low and the catalyst stability is poor, resulting in high impurity content in iron phosphate precipitation, making it difficult to meet environmentally friendly emission standards.
Using electrolytic pretreatment, Fenton oxidation, centrifugal cleaning and electrofenton oxidation steps, combined with surface-modified coated nano zero-valent iron Fenton catalyst, the formation of hydroxyl radicals through efficient pretreatment and catalyzed hydrogen peroxide, and oxidizes the Impurities in wastewater improve the recovery and purity of iron phosphate.
It significantly improves the recovery rate and purity of iron phosphate, enhances the dispersion and stability of the catalyst, ensures the high purity and stability of the product, is suitable for large-scale industrial applications, and meets strict environmental protection emission standards.
Smart Images

Figure BDA0005097531340000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial wastewater treatment and recycling, and in particular to a method for recycling iron phosphate in chemical nickel plating waste liquid. Background Art
[0002] Electroplating is a common process in the national processing and manufacturing industry, and is widely used in the fields of machinery, electronics, aerospace, etc. Chemical nickel plating is an important branch of the electroplating industry. Due to its excellent corrosion resistance, wear resistance, weldability and uniform thickness of the coating, it has been widely used worldwide. The rapid development of the chemical nickel plating industry has also brought about the problem of a large amount of chemical nickel plating waste liquid that needs to be treated. Chemical nickel plating waste liquid contains high concentrations of nickel and hypophosphite, with a content of several to tens of grams per liter. The discharge of heavy metal nickel into the water body has a significant toxic effect on aquatic organisms. When the nickel ion concentration in the water body exceeds 1.2 mg / L, it can cause the death of fish. The hypophosphite in the waste liquid is difficult to be effectively utilized by microorganisms in the biochemical treatment method. Most sewage treatment plants have serious problems of excessive phosphorus discharge due to the treatment of this stream of water. In addition, a large amount of phosphorus discharged into the water body seriously pollutes the water quality and is one of the pollutants that cause eutrophication of the water body. According to the standards in Table 3 of the current electroplating pollutant emission standards in my country (GB21900-2008), the allowable emission concentration of nickel is only 0.1 mg / L, and the allowable emission concentration of total phosphorus is 0.5 mg / L.
[0003] In the prior art, the efficient recycling of iron phosphate from chemical nickel plating waste liquid mainly has the following problems: (1) The existing recycling methods are often unable to efficiently recover phosphorus from the waste liquid, resulting in a low phosphorus recovery rate and inability to fully utilize resources. In addition, due to the complex existence of phosphorus in chemical nickel plating waste liquid, it is difficult to efficiently convert it into recyclable iron phosphate by traditional physical or chemical methods. (2) The existing catalysts are insufficient in stability, dispersibility and catalytic activity, resulting in low efficiency in the Fenton oxidation process and difficulty in effectively generating sufficient hydroxyl radicals to oxidize impurities in the waste water. (3) The existing recycling methods are not thorough enough in removing impurities from the waste liquid, resulting in a high impurity content in the final iron phosphate precipitate, affecting product quality. (4) The chemical nickel plating waste liquid contains high concentrations of nickel and hypophosphite, which is difficult to treat. The existing methods are difficult to meet the requirements of my country's current electroplating pollutant emission standards (GB 21900-2008), that is, the allowable emission concentration of nickel is 0.1 mg / L and the allowable emission concentration of total phosphorus is 0.5 mg / L.
[0004] Therefore, there is an urgent need for a method for recycling iron phosphate from chemical nickel plating waste liquid to solve the problems existing in the existing technology and provide new ideas and technical support for future environmental protection technology and waste resource technology. Summary of the invention
[0005] To this end, the present invention provides a method for recovering and utilizing iron phosphate from chemical nickel plating waste liquid to solve the problems of low iron phosphate recovery rate and insufficient catalyst stability in the prior art, and significantly improves the efficiency and purity of recovering iron phosphate from chemical nickel plating waste liquid.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] According to a first aspect of the present invention, there is provided a method for recycling iron phosphate from chemical nickel plating waste liquid, comprising the following steps:
[0008] S1. Pretreatment of chemical nickel plating waste liquid: placing the chemical nickel plating waste liquid into an electrolytic cell for electrolysis, adding calcium salt to the waste liquid after electrolysis to remove sulfate ions, and further removing nickel ions by adding sodium hydroxide solution to obtain a nickel-free waste liquid;
[0009] S2. Fenton oxidation: The nickel-removing wastewater is passed into an oxidation tank, and hydrogen peroxide and a surface-modified coated nano-zero-valent iron Fenton catalyst are added in a mass ratio of (2-8):1, and then sulfuric acid is added to adjust the pH to 2-4, thereby performing Fenton oxidation, and then the hydroxyl radicals in the Fenton oxidation are used to oxidize the complex, part of the COD and hypophosphite ions in the wastewater to obtain phosphate ions, which then react with the iron ions produced in the Fenton oxidation reaction to finally obtain iron phosphate precipitates;
[0010] S3. Centrifugation, cleaning, and recovery: Use a centrifuge to separate the iron phosphate precipitate from the wastewater. The water content of the iron phosphate precipitate filtered out is 40%. Then, water is added at a mass ratio of 1: (1-3). The surface of the iron phosphate precipitate filtered out is cleaned by a cleaning machine. The cleaning wastewater is collected together with the wastewater after the filter press.
[0011] S4. Electro-Fenton oxidation: Finally, the cleaned wastewater and the wastewater after filter pressing are passed into the electro-Fenton oxidation tank, hydrogen peroxide is added, and sulfuric acid is added to adjust the pH. After power is turned on, electro-Fenton oxidation is performed on the hypophosphite ions containing a lower concentration to obtain iron phosphate precipitate.
[0012] Furthermore, the S1 comprises the following specific steps:
[0013] S11. Electrolytic treatment: First, a titanium-based platinum electrode is used as the anode, a graphite electrode is used as the cathode, and then a pH meter is provided in the electrolytic cell, and then the chemical nickel plating waste liquid is placed in the electrolytic cell as an electrolyte for electrolytic treatment to obtain a preliminarily treated nickel-removing waste liquid;
[0014] S12. Removal of sulfate ions: The preliminarily treated nickel removal waste liquid was added with a molar ratio of 1-3 mol / L of calcium salt, stirred at 30-115 ° C for 3-12 h, and the calcium sulfate precipitate and the waste liquid after the sulfate ions were removed were filtered;
[0015] S13. Removal of nickel ions: The waste liquid after the sulfate ions are removed and a potassium hydroxide solution with a molar ratio of 2-3 mol / L are added in parallel to a reactor with a stirring device. After reacting for 10-20 hours under the conditions of a stirring speed of 300-700 rpm, a pH value of 8-12, and a temperature of 40-80°C, the nickel hydroxide precipitate and the nickel-removed waste liquid are obtained by filtration.
[0016] Furthermore, the calcium salt in S12 is one or a mixture of two or more of calcium chloride, calcium nitrate and calcium carbonate.
[0017] Furthermore, the preparation method of the surface-modified coated nano zero-valent iron Fenton catalyst in S2 comprises the following steps:
[0018] (1) preparing an iron ion mixed solution: firstly, adding a trivalent iron salt and a divalent iron salt into deionized water at a mass ratio of (1.5-3):1, then adding Tween 80 at a mass ratio of 1:(3-8) to the coated nano zero-valent iron, and stirring to fully dissolve to obtain an iron ion mixed solution;
[0019] (2) placing the iron ion mixed solution in an ultrasonic generator, adding sodium hydroxide solution dropwise while ultrasonically oscillating until the pH value of the system reaches 11-12, and then continuing ultrasonic oscillation for 10-30 minutes, and then performing magnetic separation, washing the precipitate with deionized water and ethanol multiple times to remove impurities, and drying to obtain coated nano zero-valent iron;
[0020] (3) Add the coated nano zero-valent iron to a small molecule alcohol mixture in a mass ratio of (1-3): (1-10), and ultrasonically vibrate to obtain a uniform dispersion. Then, while ultrasonically vibrating, gradually dropwise add a sodium hydroxide solution in a mass ratio of (1-10): (200-500) of the dispersion, and add ethyl orthosilicate in a mass ratio of (8-12): (1-10) to the coated nano zero-valent iron. After stirring evenly, react at 45-90° C. and 50-250 rpm / min for 3-12 hours, perform magnetic separation, and wash the product with water and ethanol in turn. After drying, obtain a surface-modified coated nano zero-valent iron Fenton catalyst.
[0021] Furthermore, the coated nano zero-valent iron in (1) has nano zero-valent iron as the core, and its surface is coated with calcium hydroxide nanoparticles.
[0022] Furthermore, the ferric iron salt and the ferrous iron salt in (1) are any one of ferric sulfate / ferrous sulfate, ferric chloride / ferrous chloride, ferric nitrate / ferrous nitrate, ferric acetate / ferrous acetate, ferric citrate / ferrous citrate, and ferrous oxalate / ferrous oxalate.
[0023] Furthermore, the small molecule alcohol in (3) is any one of ethanol, n-propanol, isopropanol, n-hexanol and n-butanol.
[0024] Furthermore, the method for preparing the coated nano zero-valent iron comprises the following steps:
[0025] 1) filling argon gas under vacuum conditions, using ultrasound to evenly disperse the nano zero-valent iron particles in anhydrous ethanol to obtain a nano zero-valent iron suspension with a concentration of 0.5-1 g / L;
[0026] 2) adding anhydrous ethanol solution of calcium chloride to the suspension obtained in step 1), wherein the mass ratio of calcium chloride to nano zero-valent iron particles is (0.5-3):1;
[0027] 3) Under continuous ultrasound and inert atmosphere, an anhydrous ethanol solution of sodium hydroxide is added to the solution obtained in step 2) at a rate of 0.1-0.5 mol / (mol Ca·min), so that the molar ratio of sodium hydroxide to calcium chloride is (2-2.5):1, and ultrasound is continued until the precipitation of calcium hydroxide nanoparticles is completely and stably coated on the surface of the nano zero-valent iron to obtain a coated nano zero-valent iron suspension;
[0028] 4) adding anhydrous ethanol to the suspension obtained in step 3) to wash and dissolve impurities in the suspension, and storing the prepared coated nano zero-valent iron material in anhydrous ethanol.
[0029] Furthermore, the mass ratio of the calcium hydroxide nanoparticles to the nano zero-valent iron is (1.3-2.5):1.
[0030] Furthermore, the particle size of the nano zero-valent iron is 10-100 nm; the particle size of the calcium hydroxide nanoparticles is 10-50 nm.
[0031] The present invention has the following advantages:
[0032] 1. This application uses the steps of electrolytic pretreatment, Fenton oxidation, centrifugal cleaning and electro-Fenton oxidation, combined with the use of surface-modified coated nano zero-valent iron Fenton catalyst, to effectively solve the problems of low iron phosphate recovery rate, high impurity content and poor catalyst stability in the prior art. This method not only significantly improves the recovery rate and purity of iron phosphate, but also enhances the dispersibility and stability of the catalyst, ensuring the high purity and stability of the final product, and is suitable for large-scale industrial applications.
[0033] 2. The present application effectively catalyzes the decomposition of hydrogen peroxide through efficient pretreatment, Fenton oxidation, centrifugation, cleaning and recovery, and electro-Fenton oxidation methods, generates more hydroxyl radicals, controls the ratio of hydrogen peroxide to catalyst, and realizes an efficient Fenton oxidation reaction, significantly oxidizes the complexes, part of the COD and hypophosphite ions in the wastewater, and finally obtains iron phosphate precipitate. The cleaned wastewater and the wastewater after filtration are treated through efficient centrifugation, cleaning and recovery, and electro-Fenton oxidation to further remove residual impurities and ensure the purity of the final product.
[0034] 3. The surface-modified coated nano zero-valent iron Fenton catalyst used in this application has high dispersibility, stability and catalytic activity, can significantly improve the recovery rate of iron phosphate and reduce the impurity content in the final iron phosphate precipitate. It not only achieves the purpose of efficiently recovering and utilizing iron phosphate from chemical nickel plating waste liquid, but also ensures the high purity and stability of the final product, with significant economic and environmental benefits. DETAILED DESCRIPTION
[0035] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention provides a method for recycling iron phosphate from chemical nickel plating waste liquid, comprising the following steps:
[0037] S1. Pretreatment of chemical nickel plating waste liquid: placing the chemical nickel plating waste liquid into an electrolytic cell for electrolysis, adding calcium salt to the waste liquid after electrolysis to remove sulfate ions, and further removing nickel ions by adding sodium hydroxide solution to obtain a nickel-free waste liquid;
[0038] S2. Fenton oxidation: The nickel-removing wastewater is passed into an oxidation tank, and hydrogen peroxide and a surface-modified coated nano-zero-valent iron Fenton catalyst are added in a mass ratio of (2-8):1, and then sulfuric acid is added to adjust the pH to 2-4, thereby performing Fenton oxidation, and then the hydroxyl radicals in the Fenton oxidation are used to oxidize the complex, part of the COD and hypophosphite ions in the wastewater to obtain phosphate ions, which then react with the iron ions produced in the Fenton oxidation reaction to finally obtain iron phosphate precipitates;
[0039] S3. Centrifugation, cleaning, and recovery: Use a centrifuge to separate the iron phosphate precipitate from the wastewater. The water content of the iron phosphate precipitate filtered out is 40%. Then, water is added at a mass ratio of 1: (1-3). The surface of the iron phosphate precipitate filtered out is cleaned by a cleaning machine. The cleaning wastewater is collected together with the wastewater after the filter press.
[0040] S4. Electro-Fenton oxidation: Finally, the cleaned wastewater and the wastewater after filter pressing are passed into the electro-Fenton oxidation tank, hydrogen peroxide is added, and sulfuric acid is added to adjust the pH. After power is turned on, electro-Fenton oxidation is performed on the hypophosphite ions containing a lower concentration to obtain iron phosphate precipitate.
[0041] Among them, S1 includes the following specific steps:
[0042] S11. Electrolytic treatment: First, a titanium-based platinum electrode is used as the anode, a graphite electrode is used as the cathode, and then a pH meter is provided in the electrolytic cell, and then the chemical nickel plating waste liquid is placed in the electrolytic cell as an electrolyte for electrolytic treatment to obtain a preliminarily treated nickel-removing waste liquid;
[0043] S12. Removal of sulfate ions: The preliminarily treated nickel removal waste liquid was added with a molar ratio of 1-3 mol / L of calcium salt, stirred at 30-115 ° C for 3-12 h, and the calcium sulfate precipitate and the waste liquid after the sulfate ions were removed were filtered;
[0044] S13. Removal of nickel ions: The waste liquid after the sulfate ions are removed and a potassium hydroxide solution with a molar ratio of 2-3 mol / L are added in parallel to a reactor with a stirring device. After reacting for 10-20 hours under the conditions of a stirring speed of 300-700 rpm, a pH value of 8-12, and a temperature of 40-80°C, the nickel hydroxide precipitate and the nickel-removed waste liquid are obtained by filtration.
[0045] Specifically, the calcium salt in S12 is one or a mixture of two or more of calcium chloride, calcium nitrate, and calcium carbonate; preferably, calcium chloride is selected in this application.
[0046] The preparation method of the surface-modified coated nano zero-valent iron Fenton catalyst in S2 comprises the following steps:
[0047] (1) preparing an iron ion mixed solution: firstly, adding a trivalent iron salt and a divalent iron salt into deionized water at a mass ratio of (1.5-3):1, then adding Tween 80 at a mass ratio of 1:(3-8) to the coated nano zero-valent iron, and stirring to fully dissolve to obtain an iron ion mixed solution;
[0048] (2) placing the iron ion mixed solution in an ultrasonic generator, adding sodium hydroxide solution dropwise while ultrasonically oscillating until the pH value of the system reaches 11-12, and then continuing ultrasonic oscillation for 10-30 minutes, and then performing magnetic separation, washing the precipitate with deionized water and ethanol multiple times to remove impurities, and drying to obtain coated nano zero-valent iron;
[0049] (3) Add the coated nano zero-valent iron to a small molecule alcohol mixture in a mass ratio of (1-3): (1-10), and ultrasonically vibrate to obtain a uniform dispersion. Then, while ultrasonically vibrating, gradually dropwise add a sodium hydroxide solution in a mass ratio of (1-10): (200-500) of the dispersion, and add ethyl orthosilicate in a mass ratio of (8-12): (1-10) to the coated nano zero-valent iron. After stirring evenly, react at 45-90° C. and 50-250 rpm / min for 3-12 hours, perform magnetic separation, and wash the product with water and ethanol in turn. After drying, obtain a surface-modified coated nano zero-valent iron Fenton catalyst.
[0050] Specifically, the coated nano zero-valent iron in (1) has nano zero-valent iron as the core, and its surface is coated with calcium hydroxide nanoparticles.
[0051] Specifically, the ferric salt and the ferrous salt in (1) are any one of the group consisting of ferric sulfate / ferrous sulfate, ferric chloride / ferrous chloride, ferric nitrate / ferrous nitrate, ferric acetate / ferrous acetate, ferric citrate / ferrous citrate, and ferrous oxalate / ferrous oxalate; preferably, the present application uses ferric sulfate / ferrous sulfate.
[0052] Specifically, the small molecule alcohol in (3) is any one of ethanol, n-propanol, isopropanol, n-hexanol, and n-butanol; preferably, ethanol is used in the present application.
[0053] The method for preparing coated nano zero-valent iron comprises the following steps:
[0054] 1) filling argon gas under vacuum conditions, using ultrasound to evenly disperse the nano zero-valent iron particles in anhydrous ethanol to obtain a nano zero-valent iron suspension with a concentration of 0.5-1 g / L;
[0055] 2) adding anhydrous ethanol solution of calcium chloride to the suspension obtained in step 1), wherein the mass ratio of calcium chloride to nano zero-valent iron particles is (0.5-3):1;
[0056] 3) Under continuous ultrasound and inert atmosphere, an anhydrous ethanol solution of sodium hydroxide is added to the solution obtained in step 2) at a rate of 0.1-0.5 mol / (mol Ca·min), so that the molar ratio of sodium hydroxide to calcium chloride is (2-2.5):1, and ultrasound is continued until the precipitation of calcium hydroxide nanoparticles is completely and stably coated on the surface of the nano zero-valent iron to obtain a coated nano zero-valent iron suspension;
[0057] 4) adding anhydrous ethanol to the suspension obtained in step 3) to wash and dissolve impurities in the suspension, and storing the prepared coated nano zero-valent iron material in anhydrous ethanol.
[0058] Specifically, the mass ratio of calcium hydroxide nanoparticles to nano zero-valent iron is (1.3-2.5):1.
[0059] Specifically, the particle size of nano zero-valent iron is 10-100 nm; the particle size of calcium hydroxide nanoparticles is 10-50 nm.
[0060] Example 1
[0061] This embodiment provides a method for recycling iron phosphate in chemical nickel plating waste liquid, comprising the following steps:
[0062] S1. Pretreatment of chemical nickel plating waste liquid: placing the chemical nickel plating waste liquid into an electrolytic cell for electrolysis, adding calcium salt to the waste liquid after electrolysis to remove sulfate ions, and further removing nickel ions by adding sodium hydroxide solution to obtain a nickel-free waste liquid;
[0063] Among them, S1 includes the following specific steps:
[0064] S11. Electrolytic treatment: First, a titanium-based platinum electrode is used as the anode, a graphite electrode is used as the cathode, and then a pH meter is provided in the electrolytic cell, and then the chemical nickel plating waste liquid is placed in the electrolytic cell as an electrolyte for electrolytic treatment to obtain a preliminarily treated nickel-removing waste liquid;
[0065] S12. Removal of sulfate ions: 2 mol / L calcium salt was added to the preliminarily treated nickel removal waste liquid in a molar ratio, and the reaction was stirred at 80 ° C for 6 h, and then the calcium sulfate precipitate and the waste liquid after the sulfate ions were removed were obtained by filtration;
[0066] S13. Removal of nickel ions: The waste liquid after the sulfate ions are removed and a potassium hydroxide solution with a molar ratio of 2.5 mol / L are added in parallel to a reactor with a stirring device. After reacting for 13 hours under the conditions of a stirring speed of 500 rpm, a pH value of 10, and a temperature of 70°C, the nickel hydroxide precipitate and the nickel-removed waste liquid are obtained by filtration.
[0067] S2. Fenton oxidation: The nickel-removing wastewater is passed into an oxidation tank, and hydrogen peroxide and a surface-modified coated nano-zero-valent iron Fenton catalyst are added in a mass ratio of 3:1, and then sulfuric acid is added to adjust the pH to 3 to perform Fenton oxidation. The hydroxyl radicals in the Fenton oxidation are then used to oxidize the complex, part of the COD and hypophosphite ions in the wastewater to obtain phosphate ions. The phosphate ions then react with the iron ions produced in the Fenton oxidation reaction to finally obtain iron phosphate precipitates;
[0068] S3. Centrifugation, cleaning, and recovery: Use a centrifuge to separate the iron phosphate precipitate from the wastewater. The water content of the iron phosphate precipitate filtered out is 40%. Then, water is added at a mass ratio of 1:2, and the surface of the iron phosphate precipitate filtered out is cleaned by a cleaning machine. The cleaning wastewater is collected together with the wastewater after the filter press.
[0069] S4. Electro-Fenton oxidation: Finally, the cleaned wastewater and the wastewater after filter pressing are passed into the electro-Fenton oxidation tank, hydrogen peroxide is added, and sulfuric acid is added to adjust the pH. After power is turned on, electro-Fenton oxidation is performed on the hypophosphite ions containing a lower concentration to obtain iron phosphate precipitate.
[0070] The preparation method of the surface-modified coated nano zero-valent iron Fenton catalyst in S2 comprises the following steps:
[0071] (1) preparing an iron ion mixed solution: first, weighing ferrous sulfate and ferrous sulfate in a mass ratio of 2:1 for trivalent iron salt and divalent iron salt, adding them to deionized water, and then adding Tween 80 in a mass ratio of 1:5 to the yield of coated nano zero-valent iron, and stirring to fully dissolve them to obtain an iron ion mixed solution;
[0072] (2) placing the iron ion mixed solution in an ultrasonic generator, adding sodium hydroxide solution dropwise while ultrasonically vibrating until the pH value of the system reaches 11, and then continuing ultrasonically vibrating for 20 minutes, and then performing magnetic separation, washing the precipitate with deionized water and ethanol multiple times to remove impurities, and drying to obtain coated nano zero-valent iron;
[0073] (3) The coated nano-zero-valent iron is added to an ethanol mixture with a mass ratio of 1:5, and ultrasonically vibrated to obtain a uniform dispersion. Then, a sodium hydroxide solution with a mass ratio of 1:300 to the mass of the dispersion is gradually added while ultrasonically vibrating, and ethyl orthosilicate with a mass ratio of 10:1 to the coated nano-zero-valent iron is added. After stirring evenly, the mixture is reacted at 70°C and 150rpm / min for 6h, and magnetic separation is performed. The product is washed with water and ethanol in turn, and dried to obtain a double-layer coated surface-modified coated nano-zero-valent iron Fenton catalyst.
[0074] The preparation method of coated nano zero-valent iron comprises the following steps:
[0075] 1) filling argon gas under vacuum conditions, using ultrasound to evenly disperse the nano zero-valent iron particles in anhydrous ethanol to obtain a nano zero-valent iron suspension with a concentration of 0.75 g / L;
[0076] 2) adding an anhydrous ethanol solution of calcium chloride to the suspension obtained in step 1), wherein the amount of calcium chloride added is 2 g relative to 1 g of nano zero-valent iron particles;
[0077] 3) Under continuous ultrasound and inert atmosphere, an anhydrous ethanol solution of sodium hydroxide is added to the solution obtained in step 2) at a rate of 0.3 mol / (mol Ca·min) to make the molar ratio of sodium hydroxide to calcium chloride be 2.25:1, and ultrasound is continued until calcium hydroxide is precipitated completely and stably coated on the surface of the nano-zero-valent iron to obtain a coated nano-zero-valent iron suspension;
[0078] Among them, the particle size of nano zero-valent iron is 50nm; the particle size of calcium hydroxide nanoparticles is 30nm;
[0079] The mass ratio of calcium hydroxide nanoparticles to nano zero-valent iron satisfies 1.8:1.
[0080] 4) adding anhydrous ethanol to the suspension obtained in step 3) to wash and dissolve impurities in the suspension, and storing the prepared coated nano zero-valent iron material in anhydrous ethanol.
[0081] Example 2
[0082] This embodiment provides a method for recycling iron phosphate in chemical nickel plating waste liquid, comprising the following steps:
[0083] S1. Pretreatment of chemical nickel plating waste liquid: placing the chemical nickel plating waste liquid into an electrolytic cell for electrolysis, adding calcium salt to the waste liquid after electrolysis to remove sulfate ions, and further removing nickel ions by adding sodium hydroxide solution to obtain a nickel-free waste liquid;
[0084] Among them, S1 includes the following specific steps:
[0085] S11. Electrolytic treatment: First, a titanium-based platinum electrode is used as the anode, a graphite electrode is used as the cathode, and then a pH meter is provided in the electrolytic cell, and then the chemical nickel plating waste liquid is placed in the electrolytic cell as an electrolyte for electrolytic treatment to obtain a preliminarily treated nickel-removing waste liquid;
[0086] S12. Removal of sulfate ions: 2 mol / L calcium salt was added to the preliminarily treated nickel removal waste liquid in a molar ratio, and the reaction was stirred at 80 ° C for 6 h, and then the calcium sulfate precipitate and the waste liquid after the sulfate ions were removed were obtained by filtration;
[0087] S13. Removal of nickel ions: The waste liquid after the sulfate ions are removed and a potassium hydroxide solution with a molar ratio of 2.5 mol / L are added in parallel to a reactor with a stirring device. After reacting for 13 hours under the conditions of a stirring speed of 500 rpm, a pH value of 10, and a temperature of 70°C, the nickel hydroxide precipitate and the nickel-removed waste liquid are obtained by filtration.
[0088] S2. Fenton oxidation: The nickel-removing wastewater is passed into an oxidation tank, and hydrogen peroxide and a surface-modified coated nano-zero-valent iron Fenton catalyst are added in a mass ratio of 5:1, and then sulfuric acid is added to adjust the pH to 3 to perform Fenton oxidation. The hydroxyl radicals in the Fenton oxidation are then used to oxidize the complex, part of the COD and hypophosphite ions in the wastewater to obtain phosphate ions. The phosphate ions then react with the iron ions produced in the Fenton oxidation reaction to finally obtain iron phosphate precipitates;
[0089] S3. Centrifugation, cleaning, and recovery: Use a centrifuge to separate the iron phosphate precipitate from the wastewater. The water content of the iron phosphate precipitate filtered out is 40%. Then, water is added at a mass ratio of 1:2, and the surface of the iron phosphate precipitate filtered out is cleaned by a cleaning machine. The cleaning wastewater is collected together with the wastewater after the filter press.
[0090] S4. Electro-Fenton oxidation: Finally, the cleaned wastewater and the wastewater after filter pressing are passed into the electro-Fenton oxidation tank, hydrogen peroxide is added, and sulfuric acid is added to adjust the pH. After power is turned on, electro-Fenton oxidation is performed on the hypophosphite ions containing a lower concentration to obtain iron phosphate precipitate.
[0091] The preparation method of the surface-modified coated nano zero-valent iron Fenton catalyst in S2 comprises the following steps:
[0092] (1) preparing an iron ion mixed solution: first, weighing ferrous sulfate and ferrous sulfate in a mass ratio of 2:1 for trivalent iron salt and divalent iron salt, adding them to deionized water, and then adding Tween 80 in a mass ratio of 1:5 to the yield of coated nano zero-valent iron, and stirring to fully dissolve them to obtain an iron ion mixed solution;
[0093] (2) placing the iron ion mixed solution in an ultrasonic generator, adding sodium hydroxide solution dropwise while ultrasonically vibrating until the pH value of the system reaches 11, and then continuing ultrasonically vibrating for 20 minutes, and then performing magnetic separation, washing the precipitate with deionized water and ethanol multiple times to remove impurities, and drying to obtain coated nano zero-valent iron;
[0094] (3) The coated nano-zero-valent iron is added to an ethanol mixture with a mass ratio of 1:5, and ultrasonically vibrated to obtain a uniform dispersion. Then, a sodium hydroxide solution with a mass ratio of 1:300 to the mass of the dispersion is gradually added while ultrasonically vibrating, and ethyl orthosilicate with a mass ratio of 10:1 to the coated nano-zero-valent iron is added. After stirring evenly, the mixture is reacted at 70°C and 150rpm / min for 6h, and magnetic separation is performed. The product is washed with water and ethanol in turn, and dried to obtain a double-layer coated surface-modified coated nano-zero-valent iron Fenton catalyst.
[0095] The preparation method of coated nano zero-valent iron comprises the following steps:
[0096] 1) filling argon gas under vacuum conditions, using ultrasound to evenly disperse the nano zero-valent iron particles in anhydrous ethanol to obtain a nano zero-valent iron suspension with a concentration of 0.75 g / L;
[0097] 2) adding an anhydrous ethanol solution of calcium chloride to the suspension obtained in step 1), wherein the amount of calcium chloride added is 2 g relative to 1 g of nano zero-valent iron particles;
[0098] 3) Under continuous ultrasound and inert atmosphere, an anhydrous ethanol solution of sodium hydroxide is added to the solution obtained in step 2) at a rate of 0.3 mol / (mol Ca·min) to make the molar ratio of sodium hydroxide to calcium chloride be 2.25:1, and ultrasound is continued until calcium hydroxide is precipitated completely and stably coated on the surface of the nano-zero-valent iron to obtain a coated nano-zero-valent iron suspension;
[0099] Among them, the particle size of nano zero-valent iron is 50nm; the particle size of calcium hydroxide nanoparticles is 30nm;
[0100] The mass ratio of calcium hydroxide nanoparticles to nano zero-valent iron satisfies 1.8:1.
[0101] 4) adding anhydrous ethanol to the suspension obtained in step 3) to wash and dissolve impurities in the suspension, and storing the prepared coated nano zero-valent iron material in anhydrous ethanol.
[0102] Example 3
[0103] This embodiment provides a method for recycling iron phosphate in chemical nickel plating waste liquid, comprising the following steps:
[0104] S1. Pretreatment of chemical nickel plating waste liquid: placing the chemical nickel plating waste liquid into an electrolytic cell for electrolysis, adding calcium salt to the waste liquid after electrolysis to remove sulfate ions, and further removing nickel ions by adding sodium hydroxide solution to obtain a nickel-free waste liquid;
[0105] Among them, S1 includes the following specific steps:
[0106] S11. Electrolytic treatment: First, a titanium-based platinum electrode is used as the anode, a graphite electrode is used as the cathode, and then a pH meter is provided in the electrolytic cell, and then the chemical nickel plating waste liquid is placed in the electrolytic cell as an electrolyte for electrolytic treatment to obtain a preliminarily treated nickel-removing waste liquid;
[0107] S12. Removal of sulfate ions: 2 mol / L calcium salt was added to the preliminarily treated nickel removal waste liquid in a molar ratio, and the reaction was stirred at 80 ° C for 6 h, and then the calcium sulfate precipitate and the waste liquid after the sulfate ions were removed were obtained by filtration;
[0108] S13. Removal of nickel ions: The waste liquid after the sulfate ions are removed and a potassium hydroxide solution with a molar ratio of 2.5 mol / L are added in parallel to a reactor with a stirring device. After reacting for 13 hours under the conditions of a stirring speed of 500 rpm, a pH value of 10, and a temperature of 70°C, the nickel hydroxide precipitate and the nickel-removed waste liquid are obtained by filtration.
[0109] S2. Fenton oxidation: The nickel-removing wastewater is passed into an oxidation tank, and hydrogen peroxide and a surface-modified coated nano-zero-valent iron Fenton catalyst are added in a mass ratio of 1:1, and then sulfuric acid is added to adjust the pH to 3 to perform Fenton oxidation. The hydroxyl radicals in the Fenton oxidation are then used to oxidize the complex, part of the COD and hypophosphite ions in the wastewater to obtain phosphate ions. The phosphate ions then react with the iron ions produced in the Fenton oxidation reaction to finally obtain iron phosphate precipitates;
[0110] S3. Centrifugation, cleaning, and recovery: Use a centrifuge to separate the iron phosphate precipitate from the wastewater. The water content of the iron phosphate precipitate filtered out is 40%. Then, water is added at a mass ratio of 1:2, and the surface of the iron phosphate precipitate filtered out is cleaned by a cleaning machine. The cleaning wastewater is collected together with the wastewater after the filter press.
[0111] S4. Electro-Fenton oxidation: Finally, the cleaned wastewater and the wastewater after filter pressing are passed into the electro-Fenton oxidation tank, hydrogen peroxide is added, and sulfuric acid is added to adjust the pH. After power is turned on, electro-Fenton oxidation is performed on the hypophosphite ions containing a lower concentration to obtain iron phosphate precipitate.
[0112] The preparation method of the surface-modified coated nano zero-valent iron Fenton catalyst in S2 comprises the following steps:
[0113] (1) preparing an iron ion mixed solution: first, weighing ferrous sulfate and ferrous sulfate in a mass ratio of 2:1 for trivalent iron salt and divalent iron salt, adding them to deionized water, and then adding Tween 80 in a mass ratio of 1:5 to the yield of coated nano zero-valent iron, and stirring to fully dissolve them to obtain an iron ion mixed solution;
[0114] (2) placing the iron ion mixed solution in an ultrasonic generator, adding sodium hydroxide solution dropwise while ultrasonically vibrating until the pH value of the system reaches 11, and then continuing ultrasonically vibrating for 20 minutes, and then performing magnetic separation, washing the precipitate with deionized water and ethanol multiple times to remove impurities, and drying to obtain coated nano zero-valent iron;
[0115] (3) The coated nano-zero-valent iron is added to an ethanol mixture with a mass ratio of 1:5, and ultrasonically vibrated to obtain a uniform dispersion. Then, a sodium hydroxide solution with a mass ratio of 1:300 to the mass of the dispersion is gradually added while ultrasonically vibrating, and ethyl orthosilicate with a mass ratio of 10:1 to the coated nano-zero-valent iron is added. After stirring evenly, the mixture is reacted at 70°C and 150rpm / min for 6h, and magnetic separation is performed. The product is washed with water and ethanol in turn, and dried to obtain a double-layer coated surface-modified coated nano-zero-valent iron Fenton catalyst.
[0116] The preparation method of coated nano zero-valent iron comprises the following steps:
[0117] 1) filling argon gas under vacuum conditions, using ultrasound to evenly disperse the nano zero-valent iron particles in anhydrous ethanol to obtain a nano zero-valent iron suspension with a concentration of 0.75 g / L;
[0118] 2) adding an anhydrous ethanol solution of calcium chloride to the suspension obtained in step 1), wherein the amount of calcium chloride added is 2 g relative to 1 g of nano zero-valent iron particles;
[0119] 3) Under continuous ultrasound and inert atmosphere, an anhydrous ethanol solution of sodium hydroxide is added to the solution obtained in step 2) at a rate of 0.3 mol / (mol Ca·min) to make the molar ratio of sodium hydroxide to calcium chloride be 2.25:1, and ultrasound is continued until calcium hydroxide is precipitated completely and stably coated on the surface of the nano-zero-valent iron to obtain a coated nano-zero-valent iron suspension;
[0120] Among them, the particle size of nano zero-valent iron is 50nm; the particle size of calcium hydroxide nanoparticles is 30nm;
[0121] The mass ratio of calcium hydroxide nanoparticles to nano zero-valent iron satisfies 1.8:1.
[0122] 4) adding anhydrous ethanol to the suspension obtained in step 3) to wash and dissolve impurities in the suspension, and storing the prepared coated nano zero-valent iron material in anhydrous ethanol.
[0123] Comparative Example 1: This example is used as a comparative example of Example 1, except that the surface-modified coated nano zero-valent iron Fenton catalyst in S2 is replaced with ordinary nano zero-valent iron, and the other steps and parameters are the same as those in Example 1.
[0124] Results
[0125] The recovery results of the embodiments and comparative examples were tested:
[0126] 1. Determination of phosphorus content in the original waste liquid: ICP-OES was used to determine the phosphorus content in the original waste liquid;
[0127] 2. Determine the phosphorus content in the recovered iron phosphate: First, dry and weigh the obtained iron phosphate precipitate, record its weight, use ICP-OES to determine the phosphorus content in the iron phosphate precipitate, and calculate the total weight of the recovered phosphorus based on the measured phosphorus content and the precipitate weight; wherein the calculation formula for the phosphorus recovery rate is: recovered phosphorus weight / phosphorus weight in chemical nickel plating waste liquid*100%, wherein the test results are shown in Table 1 below:
[0128] Table 1 Comparison of phosphorus recovery rates in ferric phosphate:
[0129] project Phosphorus recovery rate (%) Example 1 88.3 Example 2 87.7 Example 3 85.9 Comparative Example 1 69.3
[0130] 3. The impurity content in the iron phosphate in Examples 1-3 and Comparative 1-2 was measured using an ICP-5300 inductively coupled plasma spectrometer, and the test results are shown in Table 2 below:
[0131] Table 2 Comparison of impurity content in ferric phosphate
[0132]
[0133] As can be seen from Table 1, the phosphorus recovery rate in the embodiment is significantly higher than that in the comparative example, and the phosphorus recovery rate fluctuates less between 85.9% and 88.3%, showing good stability. The phosphorus recovery rate in the comparative example is between 69.3% and 71.5%, and the overall level is relatively low. The use ratio of the surface-modified coated nano zero-valent iron Fenton catalyst in the embodiment is proportional to the phosphorus recovery rate, which shows that in the technical solution adopted in Examples 1-3 of the present application, the surface-modified coated nano zero-valent iron Fenton catalyst has obvious advantages in recovering phosphorus.
[0134] Phosphorus recovery rate is an important indicator for evaluating the process of recycling iron phosphate from chemical nickel plating waste liquid. Phosphorus recovery rate directly reflects the effectiveness of recovering phosphorus from chemical nickel plating waste liquid. The higher the phosphorus recovery rate, the higher the efficiency of extracting phosphorus from the waste liquid and the higher the resource utilization rate. The recovered phosphorus finally exists in the form of iron phosphate. Therefore, the phosphorus recovery rate actually measures the efficiency of extracting phosphorus from chemical nickel plating waste liquid and converting it into iron phosphate. A high phosphorus recovery rate means that more phosphorus can be extracted from chemical nickel plating waste liquid and converted into useful iron phosphate products, which reduces resource waste and improves resource utilization efficiency. At the same time, a high phosphorus recovery rate also means reducing phosphorus emissions in wastewater, which helps environmental protection and meets strict environmental emission standards.
[0135] According to the data in Table 2, the following conclusions can be drawn: the impurity content in the iron phosphate of Examples 1-3 is relatively low, and the impurity content in the iron phosphate of Comparative Example 1 is relatively high. The surface-modified coated nano zero-valent iron Fenton catalyst used in the examples has the advantage of improved dispersibility compared to the ordinary nano zero-valent iron used in the comparative example. First, the dispersibility of nano zero-valent iron in the solution is improved by surface modification to prevent it from agglomerating. Secondly, the coating layer of calcium hydroxide nanoparticles can further improve the dispersibility of the nanoparticles and ensure their uniform distribution during the reaction. Finally, the use of surfactants can improve the stability of the nanoparticles in the solution and prevent them from losing activity due to oxidation or agglomeration. Among them, the coating layer of calcium hydroxide nanoparticles can protect the nano zero-valent iron from oxidation and extend its service life. In addition, the release of nano zero-valent iron can be controlled to enable it to exert the best catalytic effect under specific conditions.
[0136] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A method for recycling iron phosphate from chemical nickel plating waste liquid, characterized in that: The following steps are involved: S1. Pretreatment of chemical nickel plating waste liquid: placing the chemical nickel plating waste liquid into an electrolytic cell for electrolysis, adding calcium salt to the waste liquid after electrolysis to remove sulfate ions, and further removing nickel ions by adding sodium hydroxide solution to obtain a nickel-free waste liquid; S2. Fenton oxidation: The nickel-removing wastewater is passed into an oxidation tank, and hydrogen peroxide and a surface-modified coated nano-zero-valent iron Fenton catalyst are added in a mass ratio of (2-8):1, and then sulfuric acid is added to adjust the pH to 2-4, thereby performing Fenton oxidation, and then the hydroxyl radicals in the Fenton oxidation are used to oxidize the complex, part of the COD and hypophosphite ions in the wastewater to obtain phosphate ions, which then react with the iron ions produced in the Fenton oxidation reaction to finally obtain iron phosphate precipitates; S3. Centrifugation, cleaning, and recovery: Use a centrifuge to separate the iron phosphate precipitate from the wastewater. The water content of the iron phosphate precipitate filtered out is 40%. Then, water is added at a mass ratio of 1: (1-3). The surface of the iron phosphate precipitate filtered out is cleaned by a cleaning machine. The cleaning wastewater is collected together with the wastewater after the filter press. S4. Electro-Fenton oxidation: Finally, the cleaned wastewater and the wastewater after filter pressing are passed into the electro-Fenton oxidation tank, hydrogen peroxide is added, and sulfuric acid is added to adjust the pH. After power is turned on, electro-Fenton oxidation is performed on the hypophosphite ions containing a lower concentration to obtain iron phosphate precipitate.
2. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 1, characterized in that: The S1 comprises the following specific steps: S11. Electrolytic treatment: First, a titanium-based platinum electrode is used as the anode, a graphite electrode is used as the cathode, and then a pH meter is provided in the electrolytic cell, and then the chemical nickel plating waste liquid is placed in the electrolytic cell as an electrolyte for electrolytic treatment to obtain a preliminarily treated nickel-removing waste liquid; S12. Removal of sulfate ions: The preliminarily treated nickel removal waste liquid was added with a molar ratio of 1-3 mol / L of calcium salt, stirred at 30-115 ° C for 3-12 h, and the calcium sulfate precipitate and the waste liquid after the sulfate ions were removed were filtered; S13. Removal of nickel ions: The waste liquid after the sulfate ions are removed and a potassium hydroxide solution with a molar ratio of 2-3 mol / L are added in parallel to a reactor with a stirring device. After reacting for 10-20 hours under the conditions of a stirring speed of 300-700 rpm, a pH value of 8-12, and a temperature of 40-80°C, the nickel hydroxide precipitate and the nickel-removed waste liquid are obtained by filtration.
3. The method for recycling iron phosphate in chemical nickel plating waste liquid according to claim 2, characterized in that: The calcium salt in S12 is one or a mixture of two or more of calcium chloride, calcium nitrate and calcium carbonate.
4. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 1, characterized in that: The preparation method of the surface-modified coated nano zero-valent iron Fenton catalyst in S2 comprises the following steps: (1) preparing an iron ion mixed solution: firstly, adding a trivalent iron salt and a divalent iron salt into deionized water at a mass ratio of (1.5-3):1, then adding Tween 80 at a mass ratio of 1:(3-8) to the coated nano zero-valent iron, and stirring to fully dissolve to obtain an iron ion mixed solution; (2) placing the iron ion mixed solution in an ultrasonic generator, adding sodium hydroxide solution dropwise while ultrasonically oscillating until the pH value of the system reaches 11-12, and then continuing ultrasonic oscillation for 10-30 minutes, and then performing magnetic separation, washing the precipitate with deionized water and ethanol multiple times to remove impurities, and drying to obtain coated nano zero-valent iron; (3) Add the coated nano zero-valent iron to a small molecule alcohol mixture in a mass ratio of (1-3): (1-10), and ultrasonically vibrate to obtain a uniform dispersion. Then, while ultrasonically vibrating, gradually dropwise add a sodium hydroxide solution in a mass ratio of (1-10): (200-500) of the dispersion, and add ethyl orthosilicate in a mass ratio of (8-12): (1-10) to the coated nano zero-valent iron. After stirring evenly, react at 45-90° C. and 50-250 rpm / min for 3-12 hours, perform magnetic separation, and wash the product with water and ethanol in turn. After drying, obtain a surface-modified coated nano zero-valent iron Fenton catalyst.
5. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 4, characterized in that: The coated nano zero-valent iron in (1) has nano zero-valent iron as the core, and its surface is coated with calcium hydroxide nanoparticles.
6. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 5, characterized in that: The ferric iron salt and the ferrous iron salt in (1) are any one of ferric sulfate / ferrous sulfate, ferric chloride / ferrous chloride, ferric nitrate / ferrous nitrate, ferric acetate / ferrous acetate, ferric citrate / ferrous citrate, and ferric oxalate / ferrous oxalate.
7. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 4, characterized in that: The small molecule alcohol in (3) is any one of ethanol, n-propanol, isopropanol, n-hexanol and n-butanol.
8. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 5, characterized in that: The preparation method of the coated nano zero-valent iron comprises the following steps: 1) filling argon gas under vacuum conditions, using ultrasound to evenly disperse the nano zero-valent iron particles in anhydrous ethanol to obtain a nano zero-valent iron suspension with a concentration of 0.5-1 g / L; 2) adding anhydrous ethanol solution of calcium chloride to the suspension obtained in step 1), wherein the mass ratio of calcium chloride to nano zero-valent iron particles is (0.5-3):1; 3) Under continuous ultrasound and inert atmosphere, an anhydrous ethanol solution of sodium hydroxide is added to the solution obtained in step 2) at a rate of 0.1-0.5 mol / (mol Ca·min), so that the molar ratio of sodium hydroxide to calcium chloride is (2-2.5):1, and ultrasound is continued until the precipitation of calcium hydroxide nanoparticles is completely and stably coated on the surface of the nano zero-valent iron to obtain a coated nano zero-valent iron suspension; 4) adding anhydrous ethanol to the suspension obtained in step 3) to wash and dissolve impurities in the suspension, and storing the prepared coated nano zero-valent iron material in anhydrous ethanol.
9. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 8, characterized in that: The mass ratio of the calcium hydroxide nanoparticles to the nano zero-valent iron is (1.3-2.5):
1.
10. The method for recycling iron phosphate from chemical nickel plating waste liquid according to claim 8, characterized in that: The particle size of the nano zero-valent iron is 10-100 nm; the particle size of the calcium hydroxide nanoparticles is 10-50 nm.
Citation Information
Patent Citations
Surface modified nano ferroferric oxide Fenton catalyst and preparation method thereof
CN104258860A
Preparation method of coated nano zero-valent iron taking multilayer activated-carbon-coated graphene oxide composite powder as carrier
CN104587956A
Coated nanoscale zero-valent iron and preparation method and application thereof
CN110000371A
Method for preparing super-battery-grade iron phosphate by using chemical nickel-plating aging solution
CN116425134A
Cited By
Method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid
CN119859006A
A method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid
CN119859006B